Dangerous Exits : Escaping Abusive Relationships in Rural America - DeKeseredy, Walter S., 1959- (Book collections on Project MUSE., 2009)
"Decade after decade, violence against women has gained more attention from scholars, policy makers, and the general public. Social scientists in particular have contributed significant empirical and theoretical understandings to this issue. Strikingly, scant attention has focused on the victimization of women who want to leave their hostile partners. This groundbreaking work challenges the perception that rural communities are safe havens from the brutality of urban living. Identifying hidden crimes of economic blackmail and psychological mistreatment, and the complex relationship between patriarchy and abuse, Walter S. DeKeseredy and Martin D. Schwartz propose concrete and effective solutions, giving voice to women who have often suffered in silence."--Jacket.